Krisis Figur Ayah: Dampak Fatherless pada Perkembangan Individu - Ni Komang Putri Bintang Maharani (Fakultas of Psychology, Universitas Muria Kudus, 2025)
Fatherlessness is the absence of the father's role both physically and psychologically. The claim that Indonesia ranks third as a fatherless country yet to be scientifically substantiated. However, based on the data collected, topic of fatherless deserves attention. Some of the reasons are 1) The high divorce rate in Indonesia, 2) Rigid division of parenting roles, so the dominance of care is held by mothers, 3) The high number of early marriages so young men are not ready to carry out father’s role. This study aims to examine the impact of fatherlessness on individual development in Indonesia. The research method used literature review with the search terms “Fatherless” and “Father-Absence” on Google Scholar and Garuda search engines from August – December 2024. The results of the assessment show that there is an impact of fatherless from children to adults. The impact of fatherlessness on children includes: 1) Low self-control, 2) Low subjective well-being. The impact of fatherless on adolescents includes: 1) Avoidant attachment style, 2) Behavioral problems, 3) Depression. Finally, the impact of fatherless on adult individuals are: 1) Low emotional well-being, 2) Behavioral disturbance, 3) Romantic relationship problems. Further in-depth research is needed to understand the cultural implications of fatherless. Fatherless merupakan kondisi ketiadaan peran ayah dalam kehidupan anak, baik secara fisik maupun secara psikologis. Klaim bahwa Indonesia menempati urutan ketiga sebagai negara fatherless belum dapat dibuktikan secara ilmiah. Akan tetapi, berdasarkan data, topik mengenai krisis figur ayah dalam keluarga patut menjadi perhatian. Beberapa alasan yang melatarbelakangi kondisi ini adalah 1) Tingginya angka perceraian di Indonesia, 2) Adanya pembagian peran yang kaku antara ibu dan ayah sehingga dominansi pengasuhan dipegang oleh ibu, 3) Tingginya angka pernikahan dini sehingga remaja laki-laki belum siap menjalankan peran sebagai ayah. Penelitian ini bertujuan untuk mengkaji dampak dari fatherless terhadap perkembangan individu dari anak-anak hingga dewasa di Indonesia. Metode penelitian menggunakan literature review dengan kata kunci “Fatherless” dan “Father-Absence” pada mesin pencari Google Scholar dan Garuda selama Agustus – Desember 2024. Hasil pengkajian yang dilakukan menunjukkan bahwa fatherless memiliki dampak bagi individu dari usia anak-anak hingga dewasa. Adapun dampak dari fatherless terhadap anak-anak meliputi: 1) Low self-control, 2) Low subjective well-being. Dampak fatherless terhadap remaja meliputi: 1) Avoidant attachment style, 2) Behavioral Problem, 3) Depression. Terakhir, dampak dari fatherless terhadap individu dewasa yaitu: 1) Low emotional well-being, 2) Behavioral disturbance, 3) Romantic relationship problem. Perlu adanya kajian yang lebih mendalam mengenai implikasi budaya pada dampak fatherless.